2011
DOI: 10.1016/j.bbamcr.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Is mPTP the gatekeeper for necrosis, apoptosis, or both?

Abstract: Permeabilization of the mitochondrial membranes is a crucial step in apoptosis and necrosis. This phenomenon allows the release of mitochondrial death factors which trigger or facilitate different signaling cascades ultimately causing the execution of the cell. The mitochondrial permeability transition pore (mPTP) has long been known as one of the main regulators of mitochondria during cell death. mPTP opening can lead to matrix swelling, subsequent rupture of the outer membrane and a nonspecific release of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
246
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(256 citation statements)
references
References 113 publications
4
246
2
4
Order By: Relevance
“…The complexes responsible for mPT pore activity span both the inner and outer membranes of mitochondria (Kinnally et al, 2011a). Opening of mPT pore can be triggered by several factors such as oxidative stress, mitochondrial membrane depolarization, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The complexes responsible for mPT pore activity span both the inner and outer membranes of mitochondria (Kinnally et al, 2011a). Opening of mPT pore can be triggered by several factors such as oxidative stress, mitochondrial membrane depolarization, etc.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, the mitochondrial inner membrane contains several intramembrane channels; opening of these channels is tightly regulated to prevent disruption of the mitochondrial inner membrane potential and ATP synthesis [19]. The mPTP is the most notorious of these channels, and opening of the mPTP has been linked to several different forms of cell death following SCI, including necrosis, apoptosis, autophagy, and necroptosis [19][20][21][22][23].…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…The mPTP is the most notorious of these channels, and opening of the mPTP has been linked to several different forms of cell death following SCI, including necrosis, apoptosis, autophagy, and necroptosis [19][20][21][22][23]. The molecular structure of the mPTP is still up for debate, but several lines of evidence previously suggested that VDAC in the mitochondrial outer membrane, adenine nucleotide translocator in the mitochondrial inner membrane, and cyclophilin D (Cyp-D) in the mitochondrial matrix were integral proteins that comprised the mPTP, at least in part [24][25][26].…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 99%
See 1 more Smart Citation
“…Two partly interconnected apoptotic mechanisms exist; caspase-dependent classical apoptosis and caspase-independent programmed form of cell death, sometimes called necroptosis (Kinnally et al 2011;Smith and Yellon 2011). Both forms of cell death may be interconnected as caspases may lead to the activation of non-caspase proteases and vice versa.…”
Section: Introductionmentioning
confidence: 99%